Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/20503121211052436
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of difficult airway and its associated factors in pediatric patients who underwent surgery under general anesthesia: An observational study

Abstract: Background: The airway of an anesthetized patient should be secured with an artificial airway for oxygenation or ventilation. Pediatrics are not small adults which means they are different from adults both anatomically and physiologically. This study aims to determine the prevalence of difficult airway and its associated factors in pediatric patients who underwent surgery under general anesthesia in referral hospitals of Addis Ababa. Methods: A multi-centered cross-sectional study design was employed. The biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…The overall magnitude of difficult laryngoscopy was 15.6% among elective pediatric surgical patients (5-12 years), who were old enough to follow instructions, with no apparent difficult airway indicator in our study. The result of our study was higher than other studies that found 1% [7], 1.35% [8], 3% [9], 3.58% [10], 7.2% [11], and 10.4% [12] incidence of DL. In contrast, our result was lower than that of another study [13], which found a 20.8% prevalence of DL.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The overall magnitude of difficult laryngoscopy was 15.6% among elective pediatric surgical patients (5-12 years), who were old enough to follow instructions, with no apparent difficult airway indicator in our study. The result of our study was higher than other studies that found 1% [7], 1.35% [8], 3% [9], 3.58% [10], 7.2% [11], and 10.4% [12] incidence of DL. In contrast, our result was lower than that of another study [13], which found a 20.8% prevalence of DL.…”
Section: Discussioncontrasting
confidence: 92%
“…The discrepancies in the magnitude could be due to the use of different types of laryngoscopes which could affect the Cormack and Lehane grading because optimum intubation attempts are associated with alternative laryngoscope blades selection [ 23 ]. Furthermore, it could be due to the level of experience of the practitioner which could have a significant association with a difficult laryngoscopy [ 11 , 23 , 24 ], and it could also be due to differences in the patient's ethnicity, anthropology, sample size and definition of difficult laryngoscopy. In our study, there was no Cormack and Lehane grade IV, and there was also no difficult or failed intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, a relatively high percentage of underweight patients were noted to have a known difficult airway or difficult airway features which in anesthesia practice is associated with difficult direct laryngoscopy (13, 14). Furthermore, in otherwise healthy children, being underweight is associated with decreased predicted forced vital capacity and vital capacity on pulmonary function testing, which could make such individuals prone to hypoxemia and adverse events were they critically ill and in need of TI (26).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding pediatric patients, anesthesia literature suggests that body mass index (BMI) percentile is not associated with difficult intubation in children between 2 and 18 years old (10). Previous anesthesia literature covers both obesity and underweight pediatric patients, suggesting a range of influences for difficult intubations (11)(12)(13)(14). In the pediatric intensive care literature there is very little information, except for a previous NEAR4KIDS registry dataset (2010)(2011)(2012)(2013)(2014)(2015) that identified an association between increased body weight and greater odds of needing cricoid pressure at the time of TI (15).…”
mentioning
confidence: 99%